1991
DOI: 10.1002/j.2333-8504.1991.tb01380.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences Among Racial and Ethnic Groups in Mean Scores on the Gre and Sat: Longitudinal Comparisons

Abstract: If one compares racial/ethnic group differences on verbal and quantitative tests from published data on the Scholastic Aptitude Test (SAT) and Graduate Record Examinations (GRE) General Test, some group differences appear to be relatively larger (in standard deviation units) on the GRE General Test than on the SAT. The objective of this study was to undertake a retrospective, longitudinal analysis of a group of individuals who had taken both tests to see if group differences remain the same or change over time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The subgroup differences get larger when considering average GRE-Q scores; Black Americans score 1.03 standard deviations below White Americans and 1.40 standard deviations below Asian Americans. Pennock-Román (1993) found that when tracking students who took both the SAT and GRE, the racial subgroup differences stay fairly stable across time, with only a small narrowing of the gap. In addition to racial subgroup differences, there are also smaller gender differences, as women score on average, approximately half a standard deviation below men on the GRE-Q (Bleske-Rechek & Browne, 2014).…”
Section: Grementioning
confidence: 95%
See 1 more Smart Citation
“…The subgroup differences get larger when considering average GRE-Q scores; Black Americans score 1.03 standard deviations below White Americans and 1.40 standard deviations below Asian Americans. Pennock-Román (1993) found that when tracking students who took both the SAT and GRE, the racial subgroup differences stay fairly stable across time, with only a small narrowing of the gap. In addition to racial subgroup differences, there are also smaller gender differences, as women score on average, approximately half a standard deviation below men on the GRE-Q (Bleske-Rechek & Browne, 2014).…”
Section: Grementioning
confidence: 95%
“…Many psychologists in higher education are deeply concerned about issues of equity and equal opportunities (e.g., Hu, 2020). Over the years, significant concerns have been raised about the Graduate Record Examination (GRE) due to substantial score disparities, which are viewed by many as a systematic barrier to higher education for underrepresented minorities (URMs), such as Blacks, Hispanics, and low-income and/or first-generation students (Bleske-Rechek & Browne, 2014;ETS, 2012;Pennock-Román, 1993). These are legitimate and important concerns to address, as relying heavily on GRE scores as the basis for admission to graduate training programs may result in limited diversity in academia.…”
Section: Bias Fairness and Validity In Graduate Admissions: A Psychmentioning
confidence: 99%
“…The same pattern would result if the highest scoring Black students were more often left out of the GRE population because they tended to apply more frequently to medical or other professional schools than did the highest scoring NH White students. These and other possible explanations are explored in another report (Pennock-Roman, 1992).…”
Section: Discussionmentioning
confidence: 97%
“…This inference is incorrect because the SAT and GRE population data are not based on the same individuals, followed longitudinally. In fact, differences between the Black and NH White groups on SAT and ORE scores in a longitudinal data set containing both tests for each individual were analyzed, and no changes in Black-White group differences over time were found (Pennock-Roman, 1992). It would also be incorrect to infer from tables 3 and 4 that Puerto Rican students do not improve their test performance relative to that of NH White students during the college years.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent papers (Angoff & Johnson, 1988;Pennock-Roman, 1992b) are among the few that have examined changes in student performance from the senior year of high school past the last year of college for large samples of minority and majority students. Both studies, which have partially overlapping samples, found a very high degree of relationship (correlations in the mid .80s) between corresponding verbal and quantitative tests on the Scholastic Assessment Test (SAT)l and the Graduate Record Examination (GRE) General Test for individuals tested 4 to 9 years apart.…”
Section: Introductionmentioning
confidence: 99%